2016
DOI: 10.1039/c6ra23461e
|View full text |Cite
|
Sign up to set email alerts
|

Improved water barrier and mechanical properties of soy protein isolate films by incorporation of SiO2 nanoparticles

Abstract: SiO2 nanoparticles with different sizes were prepared under ultrasonic irradiation and incorporated with soy protein isolate (SPI) films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
1
23
2
Order By: Relevance
“…Compared to the SPI film, the half peak width of the SPI/nano‐SiO 2 films widened and the intensity decreased with the increase in the nano‐SiO 2 percentage due to the weak peaks of nano‐SiO 2 (Xu, Zhang, Chen, et al, ), which decreased the crystalline degree. This was similar to the conclusions of Ai et al () and Han and Wang () who found that the ordered structure in the SPI matrix was destroyed, resulting in a nonlinear decrease of crystalline degree. In the films, the ordered structure was slightly destroyed due to the interaction between the nano‐SiO 2 , glycerol, and SPI molecules, which caused the molecular motion and stretching.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to the SPI film, the half peak width of the SPI/nano‐SiO 2 films widened and the intensity decreased with the increase in the nano‐SiO 2 percentage due to the weak peaks of nano‐SiO 2 (Xu, Zhang, Chen, et al, ), which decreased the crystalline degree. This was similar to the conclusions of Ai et al () and Han and Wang () who found that the ordered structure in the SPI matrix was destroyed, resulting in a nonlinear decrease of crystalline degree. In the films, the ordered structure was slightly destroyed due to the interaction between the nano‐SiO 2 , glycerol, and SPI molecules, which caused the molecular motion and stretching.…”
Section: Resultssupporting
confidence: 91%
“…Meanwhile, the intensity of absorption peak at 1,153 cm −1 (C–O stretching vibration) enhanced and its wave number moved to a low frequency with higher contents of nano‐SiO 2 . This may be attributed to the effect of hydrogen bonds among the SiO 2 , glycerol, and SPI molecules, which made the density of the electron cloud average (Han, & Wang, ). It could be seen that the C=O stretching vibration (amide I band) and N–H bending vibration (amide II band) of films moved to a high frequency due to the electron‐induced effect, which made the protein chain further extended.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra of films were obtained by using a Fourier transform infrared (FTIR) spectrometer (Nicolet AntarisII, Thermo Fisher Scientific Co., Ltd., China) at room temperature. Scanning was performed in a range of 4,000–400 cm −1 , and a TGS (tri‐glycine sulfate) detector with a resolution of 4 cm −1 was used (Han & Wang, ). The contents of the secondary structures in films were determined using the methods of Guo et al () with the PeakFit v4.12.…”
Section: Methodsmentioning
confidence: 99%
“…The apple fruits then became to rot and the peel firmness dramatically decreased after the occurrence of respiration climacteric. In comparison with the control, the peel firmness of groups with coating was lower before the onset of the climacteric, which might be attributed to the SPI nanocomposite coatings had relatively low WVP (Han & Wang, ). Further, the downward trend of the coating groups appeared later and it is related to the control of metabolic changes and water content (Garcia et al ., ).…”
Section: Resultsmentioning
confidence: 99%